Hubungan Zat Gizi Makro dan Aktivitas Fisik dengan Indeks Massa Tubuh Mahasiswa - Khairunnisa, Zahra Rizqika; Zahrani, Azizah Nabila; Mardika, Intan Ayu; Damayanti, Silvi; Lestari, Catur Retno (Indonesian Journal of Biomedical Science and Health; Vol 2 No 2 (2022): Desember 2022DO - 10.31331/ijbsh.v2i2.2364, 2022)
Students need adequate food intake tailored to their needs, because they are the next generation that will bring good changes for a country. An important need to be considered at this time is the need for macronutrients, because if you consume macronutrients in excess will have an impact on health that causes obesity and the opportunity to develop non-communicable diseases. The factor assessed in nutritional status is physical activity, which can be defined as body movements derived from skeletal muscle and involving energy in the body. This study was to determine the relationship between macronutrient intake and physical activity with body mass index (BMI) of students. Sample taken using purposive sampling amounted to 30 respondents are students of the University of Ivet Semarang. Statistical analysis used Chi-Square test to determine the relationship of macronutrient intake and physical activity with body mass index (BMI) using SPSS software. From the results of the analysis obtained the significance value of carbohydrate intake (P=0.741), energy intake (P=0.741), protein intake (P=0.896), fat intake (P=0.907) and physical activity (P=0.726). From these results it can be concluded that in our study there was no relationship between macronutrient intake and physical activity with body mass index (BMI) of students.